The prognostic value of CD147/EMMPRIN is associated with monocarboxylate transporter 1 co-expression in gastric cancer - Pinheiro, Céline (2009)
The aim of the present work was to assess the role of monocarboxylate transporters (MCTs), namely MCT1 and MCT4 as well as MCT/CD147 co-expression in gastric tissues and evaluate their clinico-pathological significance in gastric carcinoma. For that, we analysed the immunohistochemical expression of MCT1, MCT4 and CD147, in a large series of gastric samples, including non-neoplastic, tumour and metastatic tissues. A significant decrease in MCT4 plasma membrane expression was observed from non-neoplastic to gastric primary malignant tissues and to lymph-node metastasis and both MCT1 and MCT4 correlated with CD147. Importantly, both MCT4 and CD147 were more frequently expressed in Lauren's intestinal-type tumours and MCT1/CD147 co-expression was associated with advanced gastric carcinoma, Lauren's intestinal type, TNM staging and lymph-node metastasis. Our results showed that the prognostic value of CD147 was associated with MCT1 co-expression in gastric cancer cells, supporting the view that CD147 plasma membrane activity is dependent on MCT co-expression.